197k views
11 votes
Which equation is equivalent to y = 2/3 X -6

=

A. 2x + 3y = -6

B. 3x – 2y = 6

C. 3x - 2y = 12

D. 2x – 3y = 18

User Vanny
by
5.0k points

1 Answer

10 votes

The answer would be D. 2x - 3y = 18

y = 2/3x - 6

We gotta put this equation in standard form, i think.

First, subtract the 2/3x

-2/3x + y = -6

Next, multiply the whole equation by -3 in order to make the “x” a whole number and a positive number.

2x - 3y = 18

Which equation is equivalent to y = 2/3 X -6 = A. 2x + 3y = -6 B. 3x – 2y = 6 C. 3x-example-1
User Fraber
by
5.8k points